Mapping of Mangrove Diversity in Kelurahan Tongkaina, Bunaken Sub-District, Manado - Puasa, Rio N.; Wantasen, Adnan S.; Mandagi, Stephanus V. (Sam Ratulangi University, 2018)
This research was conducted in coastal area of Tongkaina Village, Bunaken Sub-district, Manado City, North Sulawesi Province. The purpose of this study was to calculate the diversity of mangrove plants and map the zoning of mangrove species distribution in three research sites. The data collected are categorized as primary and secondary data. Primary data collection related to biophysical condition of mangrove ecosystem, including vegetation structure and area of mangrove cover in study site and further analyzed. Secondary data were collected from various literature studies, documentation and scientific papers and related legislation. Based on the obtained results, it was known that the diversity index of mangrove in Tongkaina is 1.71 which is categorized as medium in term of its diversity, because the value of H 'is greater than 1 and smaller than 3. This value means also that there was enough productivity, ecosystem condition is quite balanced, and moderate ecological pressures. The highest species diversity index was found in Sonneratia alba with an index of 0.37 and the lowest was in the Bruguiera gymnorrhiza species with index of 0.06. Mapping of mangrove species is done by taking coordinate points within quadrant at three research sites. Color degradation with rounded symbols are used to distinguish each species. The aims are designed to be able to easily distinguish between species visually and can be used as one method of mapping study on the diversity of mangroves. This study reveals the known levels of mangrove diversity are moderate. The existence of fishing activities and mooring boat by the local community contribute to mangrove land degradation. Indispensable protection or conservation through knowledge transfer and building awareness to the community, as well as providing an economic alternative for those utilizing mangrove for both household and commercial needs, in order to maintain better conditions are equally important.Keywords: Mapping, Mangrove, Diversity, TongkainaAbstrakPenelitian ini berlokasi di kawasan pesisir pantai Kelurahan Tongkaina, Kecamatan Bunaken Kota Manado Provinsi Sulawesi Utara. Tujuan dari penelitian ini yaitu untuk menghitung keanekaragaman hutan mangrove serta memetakan zonasi pembagian jenis mangrove di tiga stasiun penelitian. Data yang dikumpulkan adalah data primer dan data sekunder. Pengumpulan data primer berkaitan dengan kondisi biofisik ekosistem mangrove yaitu, struktur vegetasi dan luasan mangrove di daerah penelitian dan selanjutnya dianalisis. Kemudian data sekunder dikumpulkan dari berbagai kajian literature, dokumentasi dan tulisan-tulisan ilmiah serta peraturan perundang-undangan terkait. Pada hasil yang diperoleh diketahui nilai indeks keanekaragaman mangrove di Tongkaina adalah 1,71 dimana nilai indeks ini tergolong dalam kategori keanekaragaman sedang, karena nilai H’ lebih besar dari 1 dan lebih kecil dari 3, yang berarti produktivitas cukup, kondisi ekosistem cukup seimbang, dan tekanan ekologis sedang. Indeks Keanekaragaman spesies tertinggi didapati pada Sonneratia alba dengan nilai indeks 0,37 dan terendah ada pada spesies Bruguiera gymnorrhiza yang memiliki nilai indeks yaitu 0,06. Pemetaan jenis mangrove dilakukan dengan cara pengambilan titik koordinat pada kuadran di tiga stasiun penelitian. Degradasi warna dengan simbol bulat di pakai untuk membedakan tiap spesies. Hal ini bertujuan agar dapat dengan mudah membedakan antar spesies secara visual serta dapat dijadikan salah satu metode kajian untuk memetakan keanekaragaman mangrove. Diketahui tingkat keanekaragaman mangrove tergolong sedang. Adanya kegiatan pertambakan dan tambatan perahu masyarakat membuat lahan mangrove semakin berkurang. Sangat diperlukan adanya perlindungan atau pelestarian melalui pengetahuan dan penyadaran kepada masyarakat, serta memberikan alternatif ekonomi bagi yang memanfaatkan mangrove baik untuk kebutuhan rumah tangga ataupun komersial, demi menjaga perkembangan kondisi yang lebih baik.Kata kunci: Pemetaan, Mangrove, Keanekaragaman, Tongkaina